Respuesta :

Answer:

x = 3

Step-by-step explanation:

2(4 + 3x) + 6 = 32 ( subtract 6 from both sides )

2(4 + 3x) = 26 ( divide both sides by 2 )

4 + 3x = 13 ( subtract 4 from both sides )

3x = 9 ( divide both sides by 3 )

x = 3

As a check

substitute x = 3 into the left side of the equation and if value obtained is equal to the right side (32) then it is a solution to the equation.

2(4 + 3(3)) + 6

= 2(4 + 9) + 6

= 2(13) + 6

= 26 + 6

= 32

left side = right side

then x = 3 is the solution to the equation

Answer:

[tex] \sf \: x = 3[/tex]

Step-by-step explanation:

[tex] \sf \rightarrow \: 2(4 + 3x) + 6 = 32[/tex]

Apply the distributive property

[tex] \sf \rightarrow8 + 6x + 6 = 32[/tex]

Combine like terms

[tex] \sf \rightarrow 14 + 6x = 32[/tex]

Rearrange variables to the left side of the equation

[tex] \sf \rightarrow 6x = 32 - 14[/tex]

Calculate

[tex] \sf \rightarrow 6x = 18[/tex]

Divide both sides by the coefficient of 6

[tex] \sf \rightarrow \frac{6x}{6} = \frac{18}{6} [/tex]

Calculate

[tex] \sf \rightarrow x = \frac{18}{6} [/tex]

[tex] \sf \rightarrow \: x = 3[/tex]